Colloquial Cambodian : the complete course for beginners - Sak-Humphry, Chhany (London : Routledge, 2016)
'Colloquial Cambodian provides a step-by-step course in Cambodian as it is written and spoken today. This new edition has been developed by a linguist and an experienced Cambodian language professor and combines an accessible approach with a thorough treatment of the language, equipping learners with the essential skills needed to communicate confidently and effectively in Cambodian in a broad range of situations. No prior knowledge of the language is required'--
Includes bibliographical references and index.
Keywords: Khmer language -- Textbooks for foreign speakers -- English; Khmer language -- Conversation and phrase books -- English; Khmer language -- Spoken Khmer